Effect of Dopant Ions on the Electrical Conductivity and Microstructure of Polyaniline (Emeraldine Salt) - Catedral, M. D.; Tapia, A. K. G.; Sarmago, R. V.; Tamayo, J. P.; del Rosario, E. J. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 16 No 2 (2004), 2007)
Samples of polyaniline (emeraldine salt) were prepared with different protonic acid dopants, namely, hydrochloric acid (HCl), nitric acid (HNO3), perchloric acid (HClO4), sulfuric acid (H2SO4), and hydroiodic acid (HI). Using the two-point probe method, it was found that the samples had ohmic behaviors in which high linear coefficients were found in the range 0.9686–0.9997. On the other hand, the electrical conductivities were measured using the Van der Pauw method. The undoped sample had a conductivity of 5x10–4 S/cm. The highest conductivity of 109.04 S/cm was observed for the HClO4-doped sample, while the lowest value (0.02 S/cm) was obtained for the HI-doped sample. These conductivities were compared with the computed energy gap between the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) where it was found that they are inversely proportional to each other. Scanning electron microscopy revealed significant differences among the samples in terms of shapes and morphologies.